The shift in values among Andalusian poets between wine and asceticism as an example - Israa Mutashar AL- Khuwylidee; Dr.Raad N. Mayood (Journal of College of Education, 2024)
Andalusian society, at its most general level, lived a life almost dominated by leniency in religious and societal values   and customs until it became A clear feature in their lives.  At the same time, we have encountered a religious trend that attempts to follow the traditions of the early Muslims in imbuing their lives with a religious and moral character, which stands in contradiction to what Others knew about it. The research attempted to answer this turning point The great story that changed the path of poets and they then changed from a carefree life to an ascetic one The attempt was to trace the poetic production that depicted two contradictory realities among poets
Keywords: Asceticism - Wine - The Heights - Values